Analisis Butir Soal pada Olimpiade Matematika Tingkat Mahasiswa di STAIN Mandailing Natal - Muhammad Zia Alghar; Rina Sari Lubis; Aslamiah; Nisa Cahya Pertiwi Lubis (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to determine the quality of questions in the Mathematics Olympiad in the 2025 Geometric Competition at STAIN Mandailing Natal. The focus of the study was on ten multiple-choice questions used in the competition. This study used a quantitative approach with descriptive analysis. The research data came from the answer sheets of 64 participants who were students participating in the competition. The data were analyzed using classical statistics, including validity, reliability, difficulty level, discriminating power, and distractor effectiveness tests. The results of the analysis showed that 60% of the questions were in the valid category. The reliability test results showed that the questions had not reached the threshold set for the reliable category. The difficulty level results showed that 100% of the questions were in the difficult category, requiring high ability from participants. The discriminating power results showed that many questions were in the weak and moderate categories. Meanwhile, the distractor analysis results showed that 87.5% of the distractors functioned well. This study shows that the quality of the questions in the 2025 Geometric Competition still needs improvement. The questions need to be reviewed in order to assess the mathematical abilities of the participants more accurately.